CHRISTIAN ASHRAM MOVEMENT IN INDIA - Štipl, Zdeněk, 1976- ([S.l.])
1 online resource
Keywords: This book is one of the first to present a definitive history of the Christian Ashram Movement. It offers insights into the development of the Movement, Europe's Orientalist view of Eastern mysticism and how the concept of the "ashram" spread beyond the borders of India. Drawing extensively from ashram literature and the author's field research, the book critically analyzes the notions of inculturation in the encounter between Christianity and Hindu spirituality and ritualism. It looks at how the Movement grew out of the colonial encounter and how it evolved through the years, which was contingent on developments within Christian churches outside India. The volume also discusses the reinterpretation of the idea of the "ashram" by Christian theologians, the introduction of elite Brahmanical concepts within the Movement and the unique theological perspectives which were nurtured in these ashrams. The book offers an alternative perspective to the generally perceived history of Christianity in India. It will be of interest to scholars and researchers of religious studies, Christianity, sociology, social anthropology and religious history.